2003
DOI: 10.1103/physrevb.67.205105
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure ofα-Ga

Abstract: We have determined the electronic structure of ␣-Ga using angle-resolved photoemission from the ␣-Ga͑010͒ surface. Data were collected both at 78 K and at 273 K, i.e., below and above the temperature of the surface phase transition. We observe a number of relatively flat bands reflecting the partly covalent character of ␣-Ga. Our results agree fairly well with recent band-structure calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…The imperfection of the surface due to the presence of steps produces a rounding of the intensity behaviour in the critical region and a shift of T c . Nevertheless our estimated critical temperature is very close to the value found in photoemission measurements [4].…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The imperfection of the surface due to the presence of steps produces a rounding of the intensity behaviour in the critical region and a shift of T c . Nevertheless our estimated critical temperature is very close to the value found in photoemission measurements [4].…”
Section: Resultssupporting
confidence: 89%
“…In particular, it appears that the structure observed by STM (mainly ð2 Â 2Þ) is not compatible with the LEED pattern of the low-temperature phase reported here and in Refs. [3,4,8].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be emphasized that according to Refs. [25,26] surface states in Bi are situated very near the Fermi level, leading to reduced effective dimensionality, a fact which has not been previously taken into account.…”
mentioning
confidence: 99%
“…Experimental [9][10][11][12][13] studies showed that nanoparticle ensembles on metal surface can be used to create efficient micro-optical elements for SPP's, such as mirrors, beam splitters and interferometers. Furthermore, periodic arrays of metal surface nanoparticles have been shown to exhibit band gap properties for SPP's [14][15][16]. If such an SPP band gap structure has narrow channels free from the particles, then SPP's can be confined to and guided along these channels [16][17][18].…”
Section: Introductionmentioning
confidence: 99%